Antimicrobial stewardship in diabetic ketoacidosis: a single‐centre experience. Issue 2 (9th February 2020) - Gassiep, Ian; Bachmeier, Caroline; Hendry, Stephanie; Emeto, Theophilus I.; Armstrong, Mark; Sangla, Kunwarjit; Heather, Christopher S.
Abstract: Background: Diabetic ketoacidosis (DKA) is a common and serious complication arising predominantly in patients with type 1 diabetes mellitus. International data demonstrate that infection is one of the most common precipitating causes of DKA. Currently there are limited data regarding the role of antimicrobial stewardship (AMS) in this setting. Aim: To provide epidemiologic data regarding infections precipitating DKA, microbiological aetiology and antimicrobial prescribing practices in order to inform AMS interventions. Methods: Retrospective chart review of all type 1 diabetes mellitus DKA presentations from May 2015 to June 2018. Results: In total, 249 DKA presentations occurred in 111 patients. Suspected infection accounted for 100/249 (40%) presentations, and only 36/249 (14.5%) were proven or probable infections. Skin and soft tissue infection was the most common (9/36, 25%), followed by urinary tract infection (8/36, 22%) and respiratory tract infection (7/36, 19%). A pathogen was identified in 24/100 presumed infections and included Staphylococcus aureus (24, 46%), Klebsiella pneumoniae (4/24, 17%) and Escherichia coli (3/24, 13%). No viral pathogens were identified. Of 80 empirical antimicrobial prescriptions, 75% were inappropriate based on guideline management of the documented suspected infection. Single agent ceftriaxone was appropriately prescribed in 7/23 (30%) cases, and was most frequently prescribed overall 23/80 (29%). Conclusion: This study demonstrates a lower incidence of infection compared to most previous publications, and suggests that infection‐precipitated DKA may be over reported. Furthermore, our findings provide support for the role of AMS in the management of DKA.